Hirschsprung’s disease in a set of monozygotic twins - Berkel, İzzet (The Turkish Journal of Pediatrics, 1962)
Hirschsprung’s disease in a set of newborn twins is presented and clinical symptomatology and diagnosis of congenital megacolon is briefly reviewed.